Overexpression Sucrose Transporter Protein (Sut) and Sucrose Content In Genetically Modified Product (Gmp) Sugarcane(Saccharum officinarum L.) - Dewanti, Parawita; Okviandari, Purnama; Oktaria, Nina; Sugiharto, Bambang (UNEJ e-Proceeding, 2014)
Sucrose transporter (SUT) is a protein that functions to translocate sucrose from source to sink. Protein activity is determined by the accumulation of sucrose in sugarcane stem. The level of sucrose accumulation is also influenced by the activity ofÂ  sucrose phosphat synthase (SPS) and neutral invertase (NI) in conjunction with the synthesis and hydrolysis of sucrose. This aim of this study is to determine the sucrose transporter protein expression in Genetically Modified Product (GMP) of sugarcane.Genetically Modified Product GMP sugarcane events 1, 2, 3, 4, 5, 18, 20 and non GMP were used as materials. The analysis was performed by Western Blot method to observe the presence of SUT protein expression, stem sucrose content by resorcinol method to observe the translocation of sucrose, the SPS enzyme activity and NI that play a role in determining the accumulation of sucrose.The results showed that (1) an increase in SUT protein content in GMP plants events 2 and 18 with a protein band that is thicker than the non GMP plants, (2) SPS and invertase activity at all events GMP crop plants to increase compared to non GMP. Sucrose content of the stem at all events GMP plant to increase with age segment. The older age segments, the higher the sucroseÂ  content. Keywords: sugarcane (Saccharum officinarum L.), genetically modified product(GMP), sucrose transporter protein(SUT), sucrose